Penerapan Strategic Marketing Pada Bank Syariah Mandiri Kantor Cabang Jemur Handayani Surabaya - Ramadhani, Aprilia Kinasih Putri; Prasetyo, Ari (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
Islamic Banking in Indonesia are developing rapidly. it can be seen by the number ofÂ offices that increase from year to year. This development of islamic banking can make aÂ competition between the islamic banking. Therefore, to face the tight competition, islamicÂ banking needs the right strategic marketing that compatible with sharia principle. TheÂ strategic marketing consists of three components. They are segmenting, targeting, andÂ positioning. This research aims to know how the application of strategic marketing in BankÂ Syariah Mandiri Branch Office of Jemur Handayani Surabaya.This research is using qulitative approach with case study strategy. The datacollecting method is using direct interview with Bank Syariah Mandiri Branch Office of JemurÂ Handayaniâs office workers. The data analysis method is using descriptive qualitativeÂ approach.The result of this research shows that strategic marketing which is applied in BankÂ Syariah Mandiri Branch Office of Jemur Handayani are compatible with sharia principle.Â Market segments in Bank Syariah Mandiri Branch Office of Jemur Handayani are from lendingÂ and funding. For targeting, Bank Syariah Mandiri Branch Office of Jemur Handayani is usingÂ the full market coverage pattern. And the positioning is done by raising the quality of service.